2018
DOI: 10.1080/21645515.2018.1467684
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of individual- and community- level predictors on migrant children's primary immunization in Yiwu city, east China

Abstract: In order to achieve better vaccination coverage among migrant children in Yiwu, as well as to close the gaps and disparities of acceptability and accessibility in childhood vaccination in urban areas, policy makers should design interventions based on the factors addressed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…A previously published study [23] showed that the individual-level predictors of childhood immunization completeness among migrants are the sex of the child, the place of delivery, the mother's age, the mother's education, antenatal clinic visit, monthly household income, the number of children and distance to the nearest immunization clinics. Our study also has almost similar results among undocumented migrants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previously published study [23] showed that the individual-level predictors of childhood immunization completeness among migrants are the sex of the child, the place of delivery, the mother's age, the mother's education, antenatal clinic visit, monthly household income, the number of children and distance to the nearest immunization clinics. Our study also has almost similar results among undocumented migrants.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined based on the individual-level predictors of childhood immunization completeness among migrants (Hu et al, 2018). According to Hu et al [23], the individual-level predictors of childhood immunization completeness are the sex of the child, place of delivery, mother's age, mother's education, antenatal clinic visit, monthly household income, number of children and distance to the nearest immunization clinics. However, in our opinion, the place of delivery is the most significant factor determining childhood immunization among undocumented migrants in Sabah.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Vaccination of migrant children is a major potential safety hazard that directly affects vaccination coverage in China. 4–8 Apart from failing to ensure the immunity of migrant children against infectious diseases, it poses a certain threat to the health of local children and affects the development and effectiveness of prevention and control of various infectious diseases. 9–12…”
Section: Introductionmentioning
confidence: 99%